Heterotrimeric G protein γ subunit DEP1 is involved in hydrogen peroxide signaling and promotes aerenchyma formation in rice roots. (4th May 2021) - Chen, Yun; Chen, Yuanhua; Zhang, Yajun; Zhang, Dongping; Li, Guoming; Wei, Jiali; Hua, Xia; Lv, Bing; Liu, Lijun
ABSTRACT: Heterotrimeric G-protein α and β-subunits regulate H2 O2 -mediated aerenchyma formation. The rice G-protein γ-subunit, dense and erect panicle 1 (DEP1), is known to interact with the α-subunit and regulate nitrogen utilization and yield. However, it is unclear whether DEP1 regulates cell death for aerenchyma formation in rice roots. Using wild-type WYJ8 and its transgenic line WYJ8( DEP1 ), we confirmed that DEP1 is involved in H2 O2 -mediated aerenchyma formation. The rates of aerenchyma formation varied in different parts of the roots in both varieties, with the highest rate in the 4–7 cm segments, reaching a plateau in the 7–8 cm segments. Compared with WYJ8, the aerenchyma area and H2 O2 content in WYJ8( DEP1 ) were increased by 55.98% and 53.37%, respectively; however, the responses of aerenchyma formation to exogenous H2 O2 were basically the same in the two varieties. Diphenylene iodonium (DPI) treatment had no effect on H2 O2 production and elimination processes in WYJ8, but significantly reduced the activity of the key enzyme that catalyzes H2 O2 biosynthesis in WYJ8( DEP1 ). Importantly, exogenous H2 O2 treatment did not offset the effect of the decrease in endogenous H2 O2 level caused by DPI on aerenchyma formation. These results indicated that DEP1 enhanced H2 O2 biosynthesis and promoted the cell death of the root cortex, thus contributing to aerenchyma development in WYJ8( DEP1 ).